2009
DOI: 10.1039/b902504a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-activated droplet sorting (FADS): efficient microfluidic cell sorting based on enzymatic activity

Abstract: We describe a highly efficient microfluidic fluorescence-activated droplet sorter (FADS) combining many of the advantages of microtitre-plate screening and traditional fluorescence-activated cell sorting (FACS). Single cells are compartmentalized in emulsion droplets, which can be sorted using dielectrophoresis in a fluorescence-activated manner (as in FACS) at rates up to 2000 droplets s(-1). To validate the system, mixtures of E. coli cells, expressing either the reporter enzyme beta-galactosidase or an inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
910
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 832 publications
(932 citation statements)
references
References 32 publications
7
910
0
15
Order By: Relevance
“…4). This is in good agreement with the theoretically maximal enrichment, 28 η max , of 13 (see ESI † for calculation). This result indicates that the enzyme screening and the sorting work very well, as η max is derived assuming that the only limitation to the enrichment is the Poisson governed encapsulation of cells.…”
Section: Model Selection For α-Amylase Expressionsupporting
confidence: 89%
See 2 more Smart Citations
“…4). This is in good agreement with the theoretically maximal enrichment, 28 η max , of 13 (see ESI † for calculation). This result indicates that the enzyme screening and the sorting work very well, as η max is derived assuming that the only limitation to the enrichment is the Poisson governed encapsulation of cells.…”
Section: Model Selection For α-Amylase Expressionsupporting
confidence: 89%
“…This is also in line with the sorter error rate being on the order of 10 −4 indicating that it should not significantly affect the enrichment, which is more than ten times lower. A good agreement between η max and the actual enrichment was also reported by Fallah-Araghi et al 28 In contrast, Kintses et al (2012) 30 found an enrichment of ca. 1/20 of η max , likely due to the fact that their sorting experiment involved a library rather than a binary mixture of two strains, the library being a more difficult model system.…”
Section: Model Selection For α-Amylase Expressionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to compartmentalizing reactions, droplet-based microfluidics can also be used to encapsulate prokaryotic [14][15][16][17][18] and eukaryotic cells [19][20][21][22][23], and even the embryos of multicellular organisms [24,25], which opens up a new avenue for cell analysis. Recently, Brouzes et al [19] developed a droplet-based viability assay that permitted quantitative analysis of cell viability and growth within compartmentalized aqueous droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the limited sensitivity of absorption-based spectrophotometric assays [5][6][7]9,10] is a major handicap to significantly reducing reaction volumes. A noteworthy example of such a case is droplet-based microfluidics, which has emerged as a powerful tool for high-throughput screening in directed protein evolution [13,14]. In these experimental setups, the assay volume is minimized to 1 nl, to 1 fl, scaling down light path lengths to 1 lm.…”
mentioning
confidence: 99%